PRODUCTIVITY OF CROPS OF SPRING DURUM WHEAT DEPENDING ON FERTILIZERS AND BIOLOGICAL PRODUCTS - Жемела, Г. П.; Шевніков, Д. М. (Scientific Progress & Innovations, 2013)
The use of fertilizers and inoculation of spring durum wheat seeds by biological products positively affected on the photosynthetic efficiency of plants. Formation of wheat leaf surface depends both on the background of mineral nutrition and the use of biologocals. In areas without fertilizing seed treatment by biological products contributed to the increase of leaf area by 20.3% using polimiksobakteryn, 20.5% – diazofit, 23.9% – a mixture of these two drugs. These measures create favorable conditions for nutrition; form the optimal nutrition area of leaf apparatus and efficient photosynthetic productivity.